2009
DOI: 10.1016/j.neuroscience.2009.06.068
|View full text |Cite
|
Sign up to set email alerts
|

Social and physical environment alter cocaine conditioned place preference and dopaminergic markers in adolescent male rats

Abstract: This study was done to determine whether social and environmental factors alter cocaine reward and proteins implicated in mediating drug reward in rats during early adolescence. On postnatal day (PND) 23, rats were housed under conditions where both social (number of rats per cage) and environmental (availability of toys) factors were manipulated. Socially isolated rats were housed alone impoverished with no toys (II) or enriched with toys (IE). Social rats were housed 2 rats/cage with no toys (SI2) or with to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
63
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 50 publications
(62 reference statements)
7
63
1
Order By: Relevance
“…Whitaker et al (2013) showed that isolation during adolescence had an effect that was similar to that of repeated drug exposure, in that isolation enhanced the long-term potentiation of N-methyl-Daspartate receptor-mediated glutamatergic transmission in dopaminergic neurons. Such neurophysiological changes may explain the effects of isolation on learning about reinforcer-related stimuli that have been reported in previous studies of drugs (Zakharova et al, 2009;Kennedy et al, 2012) and SUC (Harmer and Phillips, 1998;van Den Berg et al, 1999). Nevertheless, more studies are needed to explore the relationship between the physiological and behavioral effects of early isolation to better understand the way in which social conditions affect processes that are linked to drug addiction.…”
Section: Discussionsupporting
confidence: 54%
“…Whitaker et al (2013) showed that isolation during adolescence had an effect that was similar to that of repeated drug exposure, in that isolation enhanced the long-term potentiation of N-methyl-Daspartate receptor-mediated glutamatergic transmission in dopaminergic neurons. Such neurophysiological changes may explain the effects of isolation on learning about reinforcer-related stimuli that have been reported in previous studies of drugs (Zakharova et al, 2009;Kennedy et al, 2012) and SUC (Harmer and Phillips, 1998;van Den Berg et al, 1999). Nevertheless, more studies are needed to explore the relationship between the physiological and behavioral effects of early isolation to better understand the way in which social conditions affect processes that are linked to drug addiction.…”
Section: Discussionsupporting
confidence: 54%
“…For example, neuropharmacological manipulation of rats' nucleus accumbens led to preferences for small, immediate rewards over large, delayed ones [84]. Social isolation caused the same effect in rats [85], in addition to altering levels of dopamine transporter protein in the nucleus accumbens [86]. Limbic function may be tied to captive animals' ARBs: for example, crib-biting horses had higher nucleus accumbens dopamine receptor densities than did non-crib-biters [87], and the frequency of pigs' spontaneous chain-chewing, before amphetamine administration, correlated positively with subsequent amphetamine-induced locomotion [88], an accumbens-mediated response [89].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the relative contribution of novel objects and conspecifics, a separate group is often housed in a social condition (SC) with conspecifics, but without novel objects. Some studies have varied the number of conspecifics with or without novel objects (Zakharova et al, 2009). In general, neurobehavioral differences are greater when comparing EC and IC rodents, with SC rats falling intermediate between these two extreme groups.…”
Section: B Social Influencesmentioning
confidence: 99%
“…Isolation rearing increases dopamine in the nucleus accumbens, striatum, and medial prefrontal cortex and also increases the transcription factor cAMP response element-binding in the nucleus accumbens (Green et al, 2010), suggesting an isolation-induced overactivity of basal mesolimbic function. This overactivity may be due to a decrease in DAT protein in the nucleus accumbens of IC rats (Zakharova et al, 2009), thus potentiating transynaptic dopamine signaling. In contrast to the deficit in DAT functioning in the nucleus accumbens, IC rats have enhanced DAT function in the prefrontal cortex as is evident by an increase in the maximum velocity of [ 3 H]dopamine uptake compared with EC rats (Zhu et al, 2004), an effect that involves protein kinase C (Wooters et al, 2011).…”
Section: Psychosocial Influences and Abused Drugsmentioning
confidence: 99%